Erratum: Search for new non-resonant phenomena in high-mass dilepton final states with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Klassen, Martin; et al. (Journal of high energy physics, 2021)
The Lagrangian in eq. (2.1) of JHEP 11 (2020) 005 has an erroneous factor of 1/2. The analysis code used for the results reported in the paper does not have this factor. The results remain unchanged.
The Atlas collaboration: G. Aad, F. Bartels, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, M. Mkrtchyan, P.S. Ott, A. Schoening, H.-C. Schultz-Coulon, R. Stamen, P. Starovoitov, L. Vigani, S. Weber, M. Wessels, X. Yue [und viele weitere]
Gesehen am 15.06.2021